ANALISA DISTRIBUSI KAPASITAS ALIRAN FLUIDA DI DAERAH PERCABANGAN PADA SISTEM PERPIPAAN - Eswanto Eswanto; Dian Syahputra (P3M Politeknik Negeri Indramayu, 2017)
In the industrialized world are required to review hearts always improving performance boost produced by industry, then the findings from the on lead or not separated from the machine using the tools the process piping systems hearts products in produced. Many of piping installation taken in connection the prayers only serves to review an distribution diverting fluid flow, split flow Being branched accordance desired. Singer study aims to determine the effect connectivity review Tee Against pressure losses due to the separation coefficient fluid flow The causes decrease in performance from the system. Operating singer research conducted experiments using a fluid air. Research data consist of variables differences free and bound variables. Data retrieval is done on with varying the diameter of the pipe branching That is ½ inch, ¾ inch and 1 inch. Research shows that more big diameter pipes which are used then branching coefficient Tee losses small increasingly is 0.2703 m, 0.17879 m and 0.0753 m, so that the debit value increase branching out Namely 16.8 liter / min, 17, 2 liters / min and 17.4 liters / min. The high Reynolds number variation on lead with diameter test sections, resulting in decreased total loss coefficient, (Re) 43 823, 39 985, 32719.8 And Htot 6.1667, 17.2, 17437. The increase in the Reynolds number (Re) will affect against losses pressure (h) at every connection.